What is Mimicked by Biomimicry? Synthetic Cells as Exemplifications of the Threefold Biomimicry Paradox. (1st October 2019) - Zwart, Hub
This article addresses three paradoxes of biomimicry. First of all: how can biomimicry be as old as technology as such and at the same time decidedly innovative and new? Secondly: how can biomimicry both entail a 'naturalisation' of technology and a 'technification' of nature? And finally: how can biomimicry be perceived as nature-friendly but at the same time (potentially at least) as a pervasive biotechnological assault on nature? Contemporary (technoscientific) biomimicry, I will argue, aims to mimic nature at the level of biomolecular processes and structures: contemporary biomimicry as micro-biomimicry. Moreover, building on Aristotle, Delbrück and Schrödinger, I will emphasise that what is mimicked by contemporary (technoscientific) biomimicry, in contrast to traditional (artisanal) instances of biomimicry, is not the morphological form (eidos), but rather the program or formula (logos;) of living systems. Contemporary biomimicry is 'in accordance with nature', but not in the traditional sense. Rather, building on decades of biomolecular research, it strives to reconcile nature and technology against the backdrop of advanced technicity. But biomimetics will only achieve its goals if it is not pursued purely as a technological endeavour, but complemented by an ethos of sustainability and respect for nature. These claims will be elucidated with the help of two case studies: a research project (namely the BaSyC project, launched in 2017 and aimed at producing a synthetic cell) and a science novel (namely Ian McEwan's Solar, which concerns the epistemic and moral challenges involved in artificial photosynthesis).